Government Policy in Preserving Cultural Heritage in North Aceh District - Syamsuddin Syamsuddin; Mauludi Mauludi; Tarmidi Tarmidi; Nurul Alyasin Ramadini; Zuruh Zun Natur (IHSA Institute, 2022)
The Malikussaleh tomb complex is one of the most important cultural heritages for the history of the Kingdom of Aceh, so its existence must be maintained and preserved after all. The government has an important role in changing a culture to be more advanced. The progress of the times is the result of thinking and human activities that make everything better. The purpose of this study is to analyze the Government's Policy in Preserving the Malikussaleh Tomb cultural heritage and analyze the obstacles in the preservation of the Malikussaleh tomb. The research method used is descriptive qualitative, research by collecting field data which is then discussed and analyzed with reference to the theoretical basis. The government's policy in preserving Malikussaleh's tomb has not gone well. Until now, Malikussaleh's tomb still looks neglected. The connecting road between the tombs has not been built as much as possible. The government should carry out construction on the connecting road between the tombs in the Malikussaleh tomb complex. So that visitors can more easily access the history. Whereas good tomb preservation will be profitable for regional finances. Many visitors come even from outside Aceh to find out about the history of the Pasai kingdom. Of course, the number of visitors will add to the regional asset, namely PAD. There are many obstacles faced by the government in preserving the tomb of Malikussaleh. With community participation, the government feels helped and more enthusiastic in doing conservation. The role of the community is number one for the region.